Media Magic Box Based on the Rembang Local Culture to Improve Class-A Motor Skills - Sudarti; Mochamad Widjanarko; Santoso (Journal of Psychology and Instruction, 2022)
There are still many children who still need to improve their fine motor skills. Various factors cause a lack of interest in the teacher’s learning media, so children are not interested in learning. This study aims to create magic box media based on the local culture of Rembang to improve the fine motor skills of Group A children in Kindergarten. The method in this study is research and development research using ten steps of research implementation. The analysis used in this research is the quantitative analysis and qualitative analysis. The data was collected through observation, interviews, questionnaires, documentation, and expert validation. The research subjects were 30 kindergarten students, eight teachers, and one principal. The results showed that material and media experts' validation results were deemed feasible to improve children's fine motor skills. The development of magic box media based on the local culture of Rembang effectively improves the fine motor skills of Group A children in the Heroines group with a t-test of 33.53 and a t-table of 2.022. Furthermore, an N-gain of 72.7 in this high category can be interpreted as an increase in children's fine motor skills with a fairly effective interpretation. This research implies that it is hoped that children's abilities can be increased by using magic box media based on the local culture of Rembang.